1998
DOI: 10.1111/j.1749-6632.1998.tb08272.x
|View full text |Cite
|
Sign up to set email alerts
|

cAMP‐Dependent Protein Kinase A‐Stimulated Sarcoplasmic Reticulum Function in Heart Failurea

Abstract: It is unclear whether decreased protein expression of SERCA2 (SR-Ca(2+)-ATPase) and phospholamban (PLB), or alterations in the phosphorylation state of PLB leading to increased inhibition of SERCA2 are responsible for the reduced SERCA2 function in failing human myocardium. In crude membrane preparations from patients with terminal heart failure due to idiopathic dilated cardiomyopathy (DCM) and control hearts (NF), SERCA2 activity was measured with a NADH coupled assay. Protein expression of SERCA2 and PLB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…*P Ͻ 0.05. pacing rates, being largely responsible for these changes (40). Reduced SERCA abundance (24), decreased PLB phosphorylation (46), and increased RyR (30) and L-type Ca 2ϩ channel phosphorylation (12) appear to underlie these end-stage defects. Ca 2ϩ regulation in earlier stages of the cardiac response to stress is less well understood.…”
Section: Discussionmentioning
confidence: 98%
“…*P Ͻ 0.05. pacing rates, being largely responsible for these changes (40). Reduced SERCA abundance (24), decreased PLB phosphorylation (46), and increased RyR (30) and L-type Ca 2ϩ channel phosphorylation (12) appear to underlie these end-stage defects. Ca 2ϩ regulation in earlier stages of the cardiac response to stress is less well understood.…”
Section: Discussionmentioning
confidence: 98%
“…That approach was recently attempted in a Phase 3 trial using the phosphodiesterase 3 selective inhibitor enoximone in combination with ␤-blockade to couple inhibition of ␤ 1 -AR adverse biological signaling with restoration of 16 Ser phospholamban phosphorylation, 122 which is reduced in the failing heart. 123 Although this 1854-patient clinical trial was not positive on its primary end points, it demonstrated promise in patients with the most severe LV dysfunction. 124 …”
Section: Compartmentation Of Intracellular Signaling In Microdomains mentioning
confidence: 99%
“…All these studies highlight the critical role of SERCA in abnormal Ca homeostasis and contractile dysfunction of HF. However, there are several publications that did not report any alteration in the SERCA expression level in human HF [56;82-84] and animal HF models [51;75]. Moreover, it has been shown that HF is also associated with a decrease in the PLB expression level [2;45;70], but to a lesser degree than SERCA [38;49;67].…”
Section: Mechanism Of Serca Dysfunction In Hfmentioning
confidence: 99%